Evaluation of the estrogenic properties of aqueous extracts of Tragia benthamii Baker (Euphorbiaceae) and Graptophyllum pictum (Acanthaceae) and their ability to alleviate some menopausal symptoms induced by ovariectomy in Wistar rats - Germain Jean Magloire Ketcha Wanda; sefirin Djiogue; Sosthène Onésiphore Djoussi Njimfo; Charline Florence Awounfack; Dieudonné Njamen (International Journal of Phytomedicine, 2016)
Tragia benthamii Baker (Euphorbiaceae) and Graptophyllum pictum Linn (Acanthaceae) are two Cameroonian medicinal plants traditionally used against female reproductive tract disorders, during and after the reproductive period, and as an abortifacient. Since there were no scientific data supporting the above claims and pharmacological studies characterizing their estrogenic properties, we therefore aimed to evaluate their ability to induce estrogen-like effects on primary estrogens targets, uterine, vagina and mammary gland; as well as their ability to alleviate hot flushes in ovariectomized adult rats. For this purpose, we applied a 3-day uterotrophic assay to determine the estrogenic effects of each extract and the mixture of both plants as used by traditional practitioners. The extracts were administered orally for 3 days to the 10 to 12 weeks aged ovariectomized rats. The results obtained showed that the aqueous extract of T. benthamii at the dose of 500 mg / kg BW, the aqueous extract of G. pictum at all the tested doses as well as the aqueous extract of the mixture at 275 mg / kg body weight induced a significant increase (p ˂ 0.01) of the uterine epithelium thickness. In addition, the aqueous extract of T. benthamii at the dose of 500 mg / kg BW, as well as the aqueous extract of the mixture at the doses of 50 and 275 mg / kg induced acinar development and eosinophil secretions. These results are proof of estrogen-like effects of T. benthamii and G. pictum and therefore justify the traditional use of these plants. This suggests the presence in these plants, of secondary metabolites with estrogenic properties, can induce cell proliferation, and to correct disorders of post-oophorectomy œstrogénopénia in the Wistar rats and therefore menopausal disorders.